Control óptimo de un filtro activo para la reducción de armónicos en la red eléctrica de distribución, utilizando la teoría de AKAGI. - Moya Chacón, Javier Alexander (2020)
The present research has as main objective to review the harmonic correction of an electrical distribution system to analyze the implementation of an algorithm based on the Non-Linear Optimization and Akagi theory, which deals with instantaneous active and reactive power where the currents and voltages of a Three-phase three-wire system were expressed vectorially through the use of the Clarke and Park transform while the other theory is based on getting an optimal lambda that formulate the Non-Linear Optimization model and applying the Lagrange theory, using conditions of (KKT). This research was carried out by a base model desing of a simulated electrical system in SIMULINK program implementing an active power filter that has as its main function the harmonics reduction in the electric power distribution networks. The simulations were carried out to give optimal results when the active power filter was applied, correcting notoriously the harmonics produced by the different loads that cause disturbances to the electric network.